(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Affective factors play a crucial role in the development of oral proficiency in second language learning. Among these factors, inhibition and second language ego significantly influence learners’ willingness to participate in speaking activities and their overall communicative competence. This article examines how varying levels of inhibition affect the formation of a second language ego across different age groups, with particular attention to adolescent learners. Drawing on theoretical perspectives from second language acquisition research, the study highlights the relationship between anxiety, affective filter, and oral language performance. The discussion emphasizes that high levels of inhibition and negative language ego can hinder learners’ oral development, whereas reduced anxiety and a positive second language ego facilitate effective communication. The article concludes by underscoring the importance of creating supportive, low-anxiety classroom environments that encourage risk-taking and active participation. Such pedagogical practices can help learners build confidence, reduce affective barriers, and enhance their oral proficiency in the target language.